2012
DOI: 10.1111/j.1469-7610.2012.02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced orbitofrontal and temporal grey matter in a community sample of maltreated children

Abstract: The medial orbitofrontal cortex and the middle temporal gyrus have been implicated in reinforcement-based decision-making, emotion regulation and autobiographical memory, processes that are impaired in a number of psychiatric disorders associated with maltreatment. We speculate that grey matter disturbance in these regions in a community sample of maltreated children may represent a latent neurobiological risk factor for later psychopathology and heightened risk taking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 52 publications
15
120
0
6
Order By: Relevance
“…CTQ scores were specifically associated with anterior cingulate gyrus, precuneus, and parahippocampal gyrus cortical thinning. These studies parallel morphometric work BioMed Research International 3 that has noted grey matter density and volumetric reductions in medial/prefrontal regions and cingulate in adults and children with a history of maltreatment/trauma (e.g., physical neglect) [21][22][23][24][25][26]. These structures have been implicated in emotion regulation and memory processing and tend to exhibit morphometric and functional changes in MDD.…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…CTQ scores were specifically associated with anterior cingulate gyrus, precuneus, and parahippocampal gyrus cortical thinning. These studies parallel morphometric work BioMed Research International 3 that has noted grey matter density and volumetric reductions in medial/prefrontal regions and cingulate in adults and children with a history of maltreatment/trauma (e.g., physical neglect) [21][22][23][24][25][26]. These structures have been implicated in emotion regulation and memory processing and tend to exhibit morphometric and functional changes in MDD.…”
Section: Introductionsupporting
confidence: 49%
“…Exploratory rmANOVAs (HAMD 17 scores and age as covariates; hemisphere as with-and groups as between-subject factors; significance was set at < .01) yielded a trend for an onset group × childhood trauma group interaction for superior temporal cortex thickness (F[1,25] = 5.98, = .022), with pairwise comparisons indicating a trend for a difference in cortical thickness between the pediatric ( = 8; 2.59 ± .14) and adult ( = 8; 2.77 ± .14) MDD onset groups with childhood abuse ( = .02). For frontal pole thickness, an onset group × childhood trauma group × hemisphere interaction trend existed (F [1,25] …”
Section: Two Group Analyses (Mdd Groups: Childhood Abuse Group and Nomentioning
confidence: 99%
“…17 In addition, a study of 18 maltreated children, compared with 20 nonmaltreated children, showed reduced grey matter in the medial OFC and the left middle temporal gyrus in those with maltreatment. 18 Thus, these results suggested the OFC and ACC should be included in addition to the hippocampus and DMPFC as regions of interest for the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Radiographic hippocampal changes in abused children are less pronounced than those seen in adults reporting to have experienced abuse as children, but there is evidence of reduced cortical thickness of the ventral anterior cingulate, superior frontal gyrus, and the OFC, as well as of the left middle temporal area and lingual gyrus [52]. Studies support the theory that different brain regions show unique sensitive periods to the effects of stress.…”
Section: Childhood Maltreatmentmentioning
confidence: 95%